Steel slag-based single-component geopolymer mortar and preparation method thereof
By performing high-speed ball milling of steel slag powder, silicon-aluminum solid waste and solid alkali exciter, combined with fine steel slag aggregate, the preparation process of single-component polymer mortar is simplified, and the cost of alkali excitation solutions in the prior art is solved. The problem of low activity of steel slag has achieved low cost and low carbon efficient resource utilization and improved mechanical properties.
Patent Information
- Application Number
- CN202411437715.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-01-10
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The use of alkali excitation solutions in the existing local polymer production increases cost and environmental pollution, and the content of silicon-aluminum components of steel slag is low, the gelling activity is not high, high cost pretreatment is required to improve activity, and fine aggregates are fine. The screening requirements are strict, limiting the application of steel slag in single-component polymer mortar.
The steel slag powder, silicon-aluminum solid waste blending material is mixed with solid alkali exciter and high-speed ball milling is carried out, combined with the steel slag fine aggregate, and the reaction activity of the steel slag is improved through mechanical activation to prepare a steel slag-based single-component earth polymer mortar. Simplify processes and improve resource utilization.
It significantly reduces production costs, improves the resource utilization rate of steel slag and the mechanical properties of mortar, and meets the actual engineering application needs of low-carbon green mortar materials.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, and in particular to a steel slag-based single-component geopolymer mortar and a preparation method thereof. Background Art
[0003] Geopolymer is an inorganic polymer formed by an alkali-activated reaction of an inorganic aluminosilicate precursor. Unlike traditional cement-based materials, it does not require lime or silicate as raw materials, but uses an alkali activator solution to dissolve the aluminosilicate components in the aluminosilicate precursor and undergo a polymerization reaction. The carbon dioxide produced during the production of geopolymer is significantly lower than that of traditional cement, and aluminosilicate solid waste (such as slag and fly ash) can be used as raw materials.
[0004] Traditional geopolymers are made of two parts: aluminosilicate precursors and alkali-activated solutions. The use of alkali-activated solutions not only increases production costs, but also requires special containers and conditions for its storage and transportation, increasing transportation and management costs. Although geopolymers themselves have environmental advantages, the production process of alkali-activated solutions involves high energy consumption and certain environmental pollution, which partially offsets their environmental benefits. Overall, alkali-activated solutions increase the cost and difficulty of preparation of geopolymers, limiting their practical applications.
[0005] Single-component geopolymer is a solid geopolymer material prepared by pre-mixing a solid alkali activator and a geopolymer precursor. The curing process can be started by adding water. Compared with traditional geopolymers, single-component geopolymers in solid form are easy to store and transport, reducing production costs and safety hazards. Chinese invention patent CN111548068 B discloses a single-component recycled geopolymer cement concrete, which uses fly ash, slag powder and recycled sand to prepare single-component geopolymer concrete, while not using liquid alkali activators and improving the recycling rate of solid waste. Chinese invention patent CN115974465 A discloses a lead-zinc tailings single-component geopolymer masonry mortar and its preparation method, using alkali-heat-activated lead-zinc tailings as a precursor to prepare a single-component geopolymer masonry mortar whose strength and working performance meet the requirements of actual engineering applications. However, although the above-mentioned single-component geopolymer preparation process selects relatively low-cost solid wastes such as fly ash and slag as precursors, it is necessary to use high-cost pretreatment methods such as alkali thermal activation on the raw materials to improve their reactivity, which increases the production cost. Although choosing steel slag as a precursor can significantly reduce production costs, the content of silicon and aluminum components in steel slag is relatively low, and its mineral phase crystal structure is complex and its gelling activity is not high. It needs to be preactivated to improve its activity, which partially offsets the economic benefits of using steel slag as a precursor. Therefore, a relatively low-cost activation process is needed to improve the activity of steel slag. In addition, the above-mentioned process has strict requirements on the screening of fine aggregates. If steel slag fine aggregates can be used to prepare single-component geopolymer mortar, the utilization rate of steel slag can be further improved while reducing the production cost of geopolymer mortar. Summary of the invention
[0006] In view of this, the present invention aims to provide a steel slag-based single-component geopolymer mortar, which is prepared by mixing steel slag powder, silicoaluminous solid waste admixtures and a solid alkali activator and then subjecting the mixture to high-speed ball milling to form a steel slag-based single-component geopolymer, and using steel slag fine aggregate to produce the steel slag-based single-component geopolymer mortar, which can effectively improve the resource utilization rate of steel slag and formulate a low-carbon green mortar material with performance that meets the actual engineering application.
[0007] To achieve the above object, the technical solution of the present invention is achieved as follows:
[0008] A steel slag-based single-component geopolymer mortar comprises the following components in parts by weight: 50-120 parts of steel slag powder, 30-50 parts of silicoaluminous solid waste admixture, 15-30 parts of solid alkali activator, 250-500 parts of steel slag fine aggregate and 50-100 parts of water; the steel slag-based single-component geopolymer mortar is obtained by mechanically activating a mixture of the steel slag powder, the silicoaluminous solid waste admixture and the solid alkali activator, and then adding the water and the steel slag fine aggregate and stirring.
[0009] Optionally, the fineness of the steel slag powder and the silicon-aluminum solid waste admixture are both greater than 300 mesh.
[0010] Optionally, the siliceous and aluminous solid waste admixture is one or more of slag and fly ash.
[0011] Optionally, the solid base activator is one or more of Na2SiO3, NaOH, Na2CO3 and Na2SO4.
[0012] Optionally, the steel slag fine aggregate has a particle size of less than 5 mm and a free calcium oxide content of less than 3%.
[0013] The second object of the present invention is to provide a method for preparing the above-mentioned steel slag-based single-component geopolymer mortar, the preparation method comprising the following steps:
[0014] 1) Firstly, the steel slag powder and the silicon-aluminum solid waste admixture are dried, then evenly mixed with the solid alkali activator, poured into a ball milling jar filled with steel balls and sealed, and placed on a ball mill for high-speed ball milling for a period of time to obtain a mixture A;
[0015] 2) placing the mixture A, the water and the steel slag fine aggregate in a mixer and stirring for 3-5 minutes to obtain a steel slag-based single-component geopolymer mortar.
[0016] Optionally, in step 1), the mass ratio of the total mass of the steel slag powder, the silicon-alumina solid waste admixture and the solid alkali activator to the mass of the steel ball is 1:3-5.
[0017] Optionally, the steel balls in step 1) are composed of three diameter steel balls of 8 mm, 5 mm and 3 mm in a mass ratio of 2:1-3:1-2.
[0018] Optionally, the rotation speed of the high-speed ball mill in step 1) is 400-500 r / min, and the ball milling time is 20-30 min.
[0019] Compared with the prior art, the steel slag-based single-component geopolymer mortar of the present invention has the following advantages:
[0020] 1. The single-component geopolymer preparation process of the present invention is simple and effective. Under the action of mechanochemical activation, the volcanic ash reaction activity of the steel slag powder / silica-alumina solid waste admixture is significantly improved. The prepared single-component geopolymer can be quickly solidified by adding water, and steel slag fine aggregate is used instead of natural fine aggregate to produce single-component geopolymer mortar, which further improves the resource utilization rate of steel slag.
[0021] 2. The present invention uses steel slag with a particle size of less than 5 mm as fine aggregate. Steel slag has rich angularity and higher hardness than traditional natural fine aggregate. Therefore, using steel slag fine aggregate instead of natural fine aggregate can improve the mechanical properties of mortar. In addition, steel slag is an alkaline aggregate, so it has no negative impact on the geopolymerization reaction in an alkaline environment. DETAILED DESCRIPTION
[0022] In order to enable those skilled in the art to better understand the technical solutions and technical effects of the present invention, several embodiments are provided below. Obviously, what is described below is only an embodiment and does not limit the protection scope of the present invention.
[0023] Example 1
[0024] A steel slag-based single-component geopolymer mortar comprises the following components, measured by weight: 70 parts of steel slag powder, 50 parts of slag powder, 30 parts of Na2SiO3, 450 parts of steel slag fine aggregate, and 75 parts of water, wherein the fineness of the steel slag powder and the slag powder are both 400 meshes; the particle size of the steel slag fine aggregate is less than 5 mm, and the free calcium oxide content is less than 3%.
[0025] The steel slag-based single-component geopolymer mortar is specifically prepared by the following method:
[0026] 1) Firstly, the steel slag powder and the slag powder are dried, then evenly mixed with Na2SiO3, poured into a ball mill jar filled with steel balls and sealed, placed on a ball mill and high-speed ball milled at a speed of 500r / min for 20min to obtain a mixture A, wherein the steel balls are composed of three kinds of steel balls with diameters of 8mm, 5mm and 3mm in a mass ratio of 2:3:1, and the mass ratio of the total mass of the steel slag powder, the slag powder and the Na2SiO3 to the steel balls is 1:4;
[0027] 2) Mixture A, water and steel slag fine aggregate are placed in a mixer and stirred for 3-5 minutes to obtain a steel slag-based single-component geopolymer mortar.
[0028] The prepared steel slag-based single-component geopolymer mortar was poured into a mold to make a 40mm×40mm×160mm mortar specimen. After curing for 1 day at a relative humidity of more than 95% and an ambient temperature of 20±2°C, the mold was removed and the specimen was cured for another 27 days. The strength at the curing age of 28d was 48.8MPa.
[0029] Comparative Example 1
[0030] The difference between this comparative example and Example 1 is that the fine aggregate in this comparative example is natural fine aggregate (river sand), that is, river sand is used in this comparative example to replace the steel slag fine aggregate in Example 1, and the rest is the same as Example 1.
[0031] The prepared single-component geopolymer mortar was poured into a mold to make a mortar specimen of 40mm×40mm×160mm. After curing for 1 day at a relative humidity of more than 95% and an ambient temperature of 20±2°C, the mold was removed and the specimen was cured for another 27 days. The strength at the curing age of 28d was 42.6MPa.
[0032] Comparative Example 2
[0033] The difference between this comparative example and Example 1 is that no silicon-aluminum solid waste admixture is added in this comparative example. Specifically, the comparative example includes the following components, measured by weight: 120 parts of steel slag powder, 30 parts of Na2SiO3, 450 parts of steel slag fine aggregate, and 75 parts of water.
[0034] The prepared single-component geopolymer mortar was poured into a mold to make a 40mm×40mm×160mm mortar specimen. After curing for 1 day at a relative humidity of more than 95% and an ambient temperature of 20±2°C, the mold was removed and the specimen was cured for another 27 days. The strength at the curing age of 28d was 27.8MPa.
[0035] Comparative Example 3
[0036] The difference between this comparative example and Example 1 is that no solid alkali activator is added in this comparative example. Specifically, the comparative example includes the following components in parts by weight: 100 parts of steel slag powder, 50 parts of slag powder, 450 parts of steel slag fine aggregate, and 75 parts of water.
[0037] The prepared single-component geopolymer mortar was poured into a mold to make a mortar specimen of 40mm×40mm×160mm. After curing for 1 day at a relative humidity of more than 95% and an ambient temperature of 20±2°C, the mold was removed and the specimen was cured for another 27 days. The strength at the curing age of 28d was 17.2MPa.
[0038] Comparative Example 4
[0039] The difference between this comparative example and Example 1 is that this comparative example does not use mechanical ball milling. That is, the steel slag-based single-component geopolymer mortar of this comparative example is specifically prepared by the following method:
[0040] 1) Evenly mixing dried steel slag powder and slag powder with Na2SiO3 to obtain a mixture A;
[0041] 2) Mixture A, water and steel slag fine aggregate are placed in a mixer and stirred for 3-5 minutes to obtain a steel slag-based single-component geopolymer mortar.
[0042] The prepared steel slag-based single-component geopolymer mortar was poured into a mold to make a 40mm×40mm×160mm mortar specimen. After curing for 1 day at a relative humidity of more than 95% and an ambient temperature of 20±2°C, the mold was removed and the specimen was cured for another 27 days. The strength at the curing age of 28d was 28.4MPa.
[0043] By comparing Example 1 with Comparative Example 1, it can be seen that when natural aggregate is used, the 28d compressive strength of the one-component geopolymer mortar prepared in Comparative Example 1 is reduced by 12.7% compared with that in Example 1. This shows that the addition of steel slag fine aggregate can improve the compressive strength of the steel slag-based one-component geopolymer mortar.
[0044] By comparing Example 1 and Comparative Example 2, it can be seen that without adding silicon-aluminum solid waste admixtures, the 28d compressive strength of the steel slag-based single-component geopolymer mortar prepared in Comparative Example 2 is reduced by 43% compared with Example 1. This shows that the silicon-aluminum content of steel slag is low, and the addition of silicon-aluminum solid waste admixtures can increase the active silicon-aluminum components in the geopolymer precursor, accelerate the geopolymerization reaction, and thus improve the compressive strength of the mortar.
[0045] By comparing Example 1 and Comparative Example 3, it can be seen that without adding a solid alkali activator, the 28d compressive strength of the steel slag-based single-component geopolymer mortar prepared in Comparative Example 3 is reduced by 54.4% compared with that in Example 1. This indicates that the solid alkali activator will chemically react with the steel slag and the silicon-aluminum solid waste admixture during the mechanical ball milling process, thereby improving the activity of the steel slag-based single-component geopolymer.
[0046] By comparing Example 1 and Comparative Example 4, it can be seen that without mechanical ball milling, the 28d compressive strength of the steel slag-based single-component geopolymer mortar prepared in Comparative Example 4 is reduced by 24.7% compared with that in Example 1. This shows that mechanical activation can significantly improve the geopolymerization activity of steel slag and silicon-aluminum solid waste admixtures.
[0047] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A steel slag-based one-component geopolymer mortar, characterized in that: The invention comprises the following components in parts by weight: 50-120 parts of steel slag powder, 30-50 parts of silicoaluminous solid waste admixture, 15-30 parts of solid alkali activator, 250-500 parts of steel slag fine aggregate and 50-100 parts of water; the steel slag-based single-component geopolymer mortar is prepared by mechanically activating a mixture of the steel slag powder, the silicoaluminous solid waste admixture and the solid alkali activator, and then adding the water and the steel slag fine aggregate and stirring.
2. The steel slag-based one-component geopolymer mortar according to claim 1, characterized in that: The fineness of the steel slag powder and the silicon-aluminum solid waste admixture is greater than 300 meshes.
3. The steel slag-based one-component geopolymer mortar according to claim 1, characterized in that: The silicon-alumina solid waste admixture is one or more of slag and fly ash.
4. The steel slag-based one-component geopolymer mortar according to claim 1, characterized in that: The solid base activator is one or more of Na2SiO3, NaOH, Na2CO3 and Na2SO4.
5. The steel slag-based one-component geopolymer mortar according to claim 1, characterized in that: The particle size of the steel slag fine aggregate is less than 5 mm, and the free calcium oxide content is less than 3%.
6. A method for preparing the steel slag-based one-component geopolymer mortar according to any one of claims 1 to 7, characterized in that: The following steps are involved: 1) Firstly, the steel slag powder and the silicon-aluminum solid waste admixture are dried, then evenly mixed with the solid alkali activator, poured into a ball milling jar filled with steel balls and sealed, and placed on a ball mill for high-speed ball milling for a period of time to obtain a mixture A; 2) placing the mixture A, the water and the steel slag fine aggregate in a mixer and stirring for 3-5 minutes to obtain a steel slag-based single-component geopolymer mortar.
7. The method for preparing the steel slag-based single-component geopolymer mortar according to claim 6, characterized in that: In step 1), the mass ratio of the total mass of the steel slag powder, the silicon-alumina solid waste admixture and the solid alkali activator to the mass ratio of the steel ball is 1:3-5.
8. The method for preparing the steel slag-based single-component geopolymer mortar according to claim 6, characterized in that: The steel balls in step 1) are composed of three diameter steel balls of 8 mm, 5 mm and 3 mm in a mass ratio of 2:1-3:1-2.
9. The method for preparing the steel slag-based single-component geopolymer mortar according to claim 6, characterized in that: The rotation speed of the high-speed ball mill in step 1) is 400-500 r / min, and the ball milling time is 20-30 min.
Citation Information
Patent Citations
Single-component recycled geopolymer cement concrete
CN111548068B
Lead-zinc tailing single-component geopolymer masonry mortar and preparation method thereof
CN115974465A
Geopolymer-based steel slag dry-mixed mortar binder
CN104150793A
Non-cement green mortar by using steel slag as cementing material and fine aggregate and preparation method thereof
CN105859229A
One-component alkali-activated cement
CN108516711A
Cited By
Self-heating early-strength tailing-based geopolymer
CN119822666A
An autothermal early-strength tailings geopolymer
CN119822666B